The results of changing the social and educational route of children diagnosed with moderate mental retardation and lived in stationary social services institutions - O. A. Rusakovskaya; E. A. Volodenkova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The aim of the work was to analyze the results of the correction of the social and educational rote of children, diagnosed with moderate mental retardation, receiving social services in stationary institutions for mentally disabled children. At the first stage, as a result of a continuous personal examination of 621 children living in three stationary social service institutions for children with mental disorders, 134 children were identified who presumably needed to clarify the diagnosis and change the educational and social route. At the second stage, in order to clarify the diagnosis and the educational route, a commission psychological, medical and pedagogical examination of 48 children was carried out. In 45 cases the IQ, assessed by Wechsler test, did not correspond to the diadnosis: in 24 cases the IQ was in the interval, corresponding to mild intellectual disability (50-69 points), in 21 cases IQ was above 70 points. As a result of the second stage, 26 children were transferred from a stationary social service organization for children with mental disorders to children’s homes in the education system, where they began training in adapted educational programs at a higher level. At the third stage of the study, the results of adaptation of 21 children were analyzed. It is shown that the main difficulties in the adaptation of children were not associated with the degree of intellectual impairment, but with the difficulties of transferring to an educational program of a higher level, the severity of emotional-volitional and behavioral disorders, communication disorders. It is concluded that the success of the correction of the social and educational route of children depends on the readiness of employees of educational and educational institutions to carry out rehabilitation work, the quality of psychiatric care.